The Intellectual Property Rights in Sharia Economic Law and the Fatwa of the Indonesian Ulema Council (MUI) - M Ainul Muwaffiq; Muhammad Sartibi (IRDH International Journal of Social Sciences & Humanities, 2025)
Intellectual Property Rights (IPR) hold global importance as ownership rights. A wealth of research on Intellectual Property Rights (IPR) has been conducted from both positive legal and economic perspectives. This study employs normative juridical research with a legislative approach. In the context of Sharia economics, intellectual property rights (IPR) are seen as individual rights that must be protected and used in accordance with Sharia principles, as they are regarded as gifts from Allah, the ultimate rights owner. During the VII MUI National Conference from July 19-22, 2005, the Indonesian Ulema Council issued Fatwa No. 1/MUNAS VII/MUI/5/2005 to address the rise in Intellectual Property Rights (IPR) violations. . In Islam, intellectual property rights are considered property (mal) that must be safeguarded. Taking such rights without permission is deemed haram (forbidden).